Improving patient specific quality assurance for image registration: clinical use case of target contouring for PET deformable image registration - Johnson Yuen; Joel Poder; Michael Jameson; Laurel Schmidt; Ryan Brown; Charlotte Atkinson; Shrikant Deshpande; Anna Ralston; Lois Holloway (Physical and Engineering Sciences in Medicine, 2025)
Deformable image registration (DIR) has proven to be an invaluable tool to maximize the clinical benefits of multimodality imaging in radiation oncology. In contrast to rigid image registration (RIR), which is employed at all stages of diagnosis and treatment, the uptake of DIR has been constrained by concerns over the potential for unsafe use. The AAPM Task Group 132 (TG132) published a report on the use of image registration, including many recommendations on clinical integration of registration in treatment planning and delivery. There is a remaining uncertainty on incorporating registration uncertainties into treatment margins (Sect. 6.A, TG 132), a challenge in clinical practice. The aim of this work was to report our experience in implementing a practical, patient specific quality assurance process based on the AAPM Task Group 132 report recommendations. This work includes refining our process of target contouring using PET with deformable image registration based on our experience of addressing vulnerabilities identified during implementation. A multidisciplinary team created a flowchart for patient specific quality assurance for image registration (RIR or DIR) based on use cases defined in the AAPM TG132 Report on the use of image registration in radiotherapy. Vulnerabilities identified from this implementation were assessed relative to AAPM TG132 recommendations. These findings were used to adapt our patient specific quality assurance to mitigate vulnerabilities. The main vulnerabilities were identified in the last steps of image registration. There was potential for inappropriate use of the registration for clinical use, such as target contouring where the image registration accuracy level was poor. Vulnerabilities were addressed by an adaptation in our quality assurance process. A new physics image registration QA task was introduced that independently checks registration accuracy and appropriateness of target contouring, addressing the vulnerability in the last steps of the AAPM TG132 flowchart. A multi-disciplinary team implemented the image registration process outlined by AAPM TG132. An improved patient specific quality assurance process was developed by introducing an independent physics image registration review that considers the acceptable registration uncertainty for the specific clinical use case in question.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

A camera based method for assessing surf amenity of submerged nearshore structures in a wave basin by quantifying wave breaking - Michael E. Thompson; Alex Atkinson; Evan Watterson; Nick Naderi; Heiko Loehr; Tom E. Baldock (Ocean Engineering, 2023)

Real-World Evidence of the Top 100 Prescribed Drugs in the USA and Their Potential for Drug Interactions with Nirmatrelvir; Ritonavir - Jacqueline Gerhart; Florin Draica; Michael Benigno; Jo Atkinson; Maya Reimbaeva; Domenick Francis; Nathalie Baillon-Plot; Gurinder Singh Sidhu; Bharat D. Damle (The AAPS Journal, 2023)
Nirmatrelvir (coadministered with ritonavir as PAXLOVID TM ) reduces the risk of COVID-19-related hospitalizations and all-cause death in individuals with mild-to-moderate COVID-19 at high risk of progression to severe disease. Ritonavir is coadministered as a pharmacokinetic enhancer. However, ritonavir may cause drug-drug interactions (DDIs) due to its interactions with various drug-metabolizing enzymes and transporters, including cytochrome P450 (CYP) 3A, CYP2D6, and P-glycoprotein transporters. To better understand the extent of DDIs (or lack thereof) of nirmatrelvir; ritonavir in a clinical setting, this study used real-world evidence (RWE) from the Optum Clinformatics Data Mart database to identify the top 100 drugs most commonly prescribed to US patients at high risk of progression to severe COVID-19 disease. The top 100 drugs were identified based on total counts associated with drugs prescribed to high-risk patients (i.e., ≥ 1 medical condition associated with an increased risk of severe COVID-19) who were continuously enrolled in the database throughout 2019 and had ≥ 1 prescription claim. Each of the 100 drugs was then assessed for DDI risk based on their metabolism, excretion, and transport pathways identified from available US prescribing and medical literature sources. Seventy drugs identified were not expected to have DDIs with nirmatrelvir; ritonavir, including many cardiovascular agents, anti-infectives, antidiabetic agents, and antidepressants. Conversely, 30 drugs, including corticosteroids, narcotic analgesics, anticoagulants, statins, and sedatives/hypnotics, were expected to cause DDIs with nirmatrelvir; ritonavir. This RWE analysis is complementary to the prescribing information and other DDI management tools for guiding healthcare providers in managing DDIs. Graphical Abstract

Differential Strigeid Infection Patterns in Male Morphotypes of Bluegill Sunfish (Lepomis macrochirus) - Erin Atkinson; Brandi Griffith Keller; Nicholas S. Strait; Victoria L. Krist; Michael R. Zimmermann (Acta Parasitologica, 2023)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Drivers of ecosystem vulnerability to Corbicula invasions in southeastern North America - Noé Ferreira-Rodríguez; Michael Gangloff; Gregory Shafer; Carla L. Atkinson (Biological Invasions, 2022)
Invasive species introduction is one of the major ongoing ecological global crises. Identifying factors responsible for the success of invasive species is key for the implementation of effective management actions. The invasive filter-feeding bivalve, Corbicula , is of particular interest because it has become ubiquitous in many river basins across North America and elsewhere. Here we sampled bivalve assemblages, environmental indicators, and land cover parameters in the Ouachita highlands in southeastern Oklahoma and southwestern Arkansas, and in the Gulf Coastal Plain of Alabama to test three working models (using structural equation modeling, SEM) based on a priori scientific knowledge regarding Corbicula invasions. Our models tested three competing hypotheses: (1) Native mussel declines are related to land use changes at the watershed level and subsequent Corbicula colonization is a result of an empty niche; (2) Corbicula abundance is one of the factors responsible for native mussel declines and has an interactive effect with land use change at the watershed level; (3) Native mussel declines and Corbicula success are both related to land use changes at the watershed level. We found no evidence for the first two hypotheses. However, we found that environmental indicators and land cover parameters at the watershed scale were robust predictors of Corbicula abundance. In particular, agricultural land cover was positively related with Corbicula density. These results suggest that further improvement of conventional agricultural practices including the optimization of fertilizer delivery systems may represent an opportunity to manage this species by limiting nutrient inputs to stream ecosystems. Preservation of extensive floodplain habitats may help buffer these inputs by providing key ecosystem services including sediment and nutrient retention.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

First report of luminous stimuli eliciting sound production in weevils - Carol L. Bedoya; Ximena J. Nelson; Michael Hayes; Richard W. Hofstetter; Thomas H. Atkinson; Eckehard G. Brockerhoff (The Science of Nature, 2019)

Will a warmer and wetter future cause extinction of native H awaiian forest birds? - Wei Liao; Oliver Elison Timm; Chunxi Zhang; Carter T. Atkinson; Dennis A. LaPointe; Michael D. Samuel (Global Change Biology, 2015)
Isolation of the Hawaiian archipelago produced a highly endemic and unique avifauna. Avian malaria ( Plasmodium relictum ), an introduced mosquito‐borne pathogen, is a primary cause of extinctions and declines of these endemic honeycreepers. Our research assesses how global climate change will affect future malaria risk and native bird populations. We used an epidemiological model to evaluate future bird–mosquito–malaria dynamics in response to alternative climate projections from the Coupled Model Intercomparison Project. Climate changes during the second half of the century accelerate malaria transmission and cause a dramatic decline in bird abundance. Different temperature and precipitation patterns produce divergent trajectories where native birds persist with low malaria infection under a warmer and dryer projection ( RCP 4.5), but suffer high malaria infection and severe reductions under hot and dry ( RCP 8.5) or warm and wet (A1B) futures. We conclude that future global climate change will cause significant decreases in the abundance and diversity of remaining Hawaiian bird communities. Because these effects appear unlikely before mid‐century, natural resource managers have time to implement conservation strategies to protect this unique avifauna from further decimation. Similar climatic drivers for avian and human malaria suggest that mitigation strategies for Hawai'i have broad application to human health.

Informed Decision-Making and Satisfaction with a Church-Based Men’s Health Workshop Series for African-American Men: Men-Only vs. Mixed-Gender Format - Cheryl L. Holt; Daisy Le; Darlene R. Saunders; Min Qi Wang; Jimmie L. Slade; Bettye Muwwakkil; Ralph Williams; Nancy L. Atkinson; Tony L. Whitehead; Michael Naslund (Journal of Cancer Education, 2015)

Effects of two contrasting canopy manipulations on growth and water use of London plane (Platanus x acerifolia) trees - Neil A. Hipps; Michael J. Davies; Joel M. Dunn; Howard Griffiths; Christopher J. Atkinson (Plant and Soil, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Synthesis and evaluation of p-N,N-dialkyl substituted chalcones as anti-cancer agents - Grady Nelson; Mohammad A. Alam; Tyler Atkinson; Shirisha Gurrapu; J. Sravan Kumar; Chris Bicknese; Joseph L. Johnson; Michael Williams (Medicinal Chemistry Research, 2013)

Sex hormones and skeletal muscle weakness - Sarianna Sipilä; Marco Narici; Michael Kjaer; Eija Pöllänen; Ross A. Atkinson; Mette Hansen; Vuokko Kovanen (Biogerontology, 2013)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Development of Rhizoctonia solani on Stems, Stolons and Tubers of Potato II. Efficacy of Chemical Applications - Dennis Atkinson; Michael K. Thornton; Jeffery S. Miller (American Journal of Potato Research, 2011)

Development of Rhizoctonia solani on Stems, Stolons and Tubers of Potatoes I. Effect of Inoculum Source - Dennis Atkinson; Michael K. Thornton; Jeffery S. Miller (American Journal of Potato Research, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Longitudinal size distributions of bluegill bullies (Gobiomorphus hubbsi) and torrentfish (Cheimarrichthys fosteri) in two large New Zealand rivers - Nicola K. Atkinson; Michael K. Joy (New Zealand Journal of Marine and Freshwater Research, 2009)
This study compared the longitudinal size distribution of bluegill bullies ( Gobiomorphus hubbsi ) from Hutt River with existing data on the size distributions of bluegill bullies and torrentfish ( Cheimarrichthys fosteri) from Rakaia River, New Zealand. All populations had longitudinal trajectories that showed some increase in size with distance upstream. This increase in size appeared to primarily reflect the influence of amphidromous life styles, where juveniles diffuse upstream from the sea. However, a quantile regression analysis revealed differences in growth and migration rate between the two bluegill bully populations; bluegill bullies from Rakaia River grew at a slower rate and showed variation in migration rate within their population that was not evident in the Hutt River population. Null models were also generated for each population to test for the presence of all size classes of fish in the lower reaches of each river. Both bluegill bully populations showed a significant absence of the largest size classes in the lower reaches and the size trajectories differed significantly from the null models. This difference suggests that all individual bluegill bullies continuously move upstream throughout their lives. In comparison, the size distribution of torrentfish closely resembled the null model, indicating that some individuals did not migrate upstream to the same extent as others.

Irrigation scheduling and irrigation systems: optimising irrigation efficiency for container ornamental shrubs - Olga M. Grant; Michael J. Davies; Helen Longbottom; Christopher J. Atkinson (Irrigation Science, 2009)

Response of Gobiomorphus hubbsi (bluegill bully) to odours of conspecific fish in the presence of natural stream odours: Does habitat have an influence? - Nicola K. Atkinson; Michael K. Joy (New Zealand Journal of Marine and Freshwater Research, 2008)
This study tested the ability of bluegill bullies ( Gobiomorphus hubbsi ) to detect and respond to the odour of conspecific fish upstream under neutrally odoured (rainwater) and naturally odoured (stream water) conditions. Bluegill bullies were presented with a choice of two flows of water to move into, one of which contained the odour of conspecific fish. Bluegill bullies displayed a concentration‐dependent reaction under neutral water conditions, where they were attracted to low concentrations of conspecific odour, but repelled by high concentrations of odour. This result was not consistent under naturally odoured water conditions, where no attraction towards conspecific odour occurred at low odour concentrations and only a weak avoidance of odour occurred at high concentrations. The differences revealed between natural and neutral water trials suggest the use of habitat odours over conspecific odours and cast doubt on previous studies only conducted under neutral conditions.

Impact of changing diet regimes on Steller sea lion body condition - Shannon Atkinson; Donald Calkins; Vladimir Burkanov; Michael Castellini; Daniel Hennen; Susan Inglis (Marine Mammal Science, 2008)
A leading theory for the cause of the decline of Steller sea lions is nutritional stress, which led to chronic high juvenile mortality and possibly episodic adult mortality. Nutritional stress may have resulted from either poor quality or low abundance of prey. The objective of this study was to determine whether we could predict shifts in body condition ( i.e. , body mass or body fat content) over different seasons associated with a change in diet ( i.e. , toward lower quality prey). Captive Steller sea lions ( n = 3) were fed three different diet regimes, where Diet 1 approximated the diet in the Kodiak area in the 1970s prior to the documented decline in that area, Diet 2 approximated the species composition in the Kodiak area after the decline had begun, and Diet 3 approximated the diet in southeast Alaska where the Steller sea lion population has been increasing for over 25 yr. All the animals used in this study were still growing and gained mass regardless of diet. Body fat (%) varied between 13% and 28%, but was not consistently high or low for any diet regime or season. Mean intake (in kg) of Diet 2 was significantly greater for all sea lions during all seasons. All animals did, however, tend to gain less body mass on Diets 2 and 3, as well as during the breeding and postbreeding seasons. They also tended to gain more mass during the winter and on Diet 1, though these differences were not statistically significant. Thus, changing seasonal physiology of Steller sea lions appears to have more impact on body condition than quality of prey, provided sufficient quantity of prey is available. Steller sea lions are opportunistic predators and are evidently able to thrive on a variety of prey. Our results indicate that Steller sea lions are capable of compensating for prey of low quality.

Synchronicity in Climate and Vegetation Transitions Between Europe and North America During the Holocene - K. Gajewski; André E. Viau; Michael Sawada; David E. Atkinson; Philippe Fines (Climatic Change, 2006)

Characteristics of Resuspension, Settling and Diffusion of Particulate Matter in a Water Column - Michael Belinsky; Hillel Rubin; Yehuda Agnon; Eliezer Kit; Joseph F. Atkinson (Environmental Fluid Mechanics, 2005)

Mapping of a novel MEN-like syndrome locus to rat Chromosome 4 - Kamilla Piotrowska; Natalia S. Pellegata; Michael Rosemann; Andreas Fritz; Jochen Graw; Michael J. Atkinson (Mammalian Genome, 2004)

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

Ammonium excretion by Antarctic krill Euphausia superba at South Georgia - Angus Atkinson; Michael J. Whitehouse (Limnology and Oceanography, 2000)

Ammonium excretion by Antarctic krill Euphausia superba at South Georgia - Angus Atkinson; Michael J. Whitehouse (Limnology and Oceanography, 2000)
Excretion by Antarctic krill Euphausia superba (hereafter “krill”) is measured typically in small containers of filtered seawater for 12–24 h, which may cause a reduction of swimming, feeding, and metabolism. If the maximum published excretion rates are realistic, krill would be a major source of regenerated nitrogen in the South Georgia area because of their high biomass there. Because literature values are variable, depending on season, feeding history and the experimental set‐up, our aim was to measure both a mean and an upper value of krill excretion rate at South Georgia. Experiments were on juvenile krill during October–November 1997 and January 1998. Freshly caught animals excreted 1.6–2.8 nmol ammonium mg −1 dry mass h −1 ; within the fivefold range of summer literature values for equivalent‐sized krill. Maximum rates were determined on acclimated krill in large containers during alternating 1‐d periods with and without food. During the feeding periods in saturating food concentrations, the mean daily ration was ~32% of body carbon d −1 and excretion was 210% (October–November) and 280% (January) of the values for freshly caught krill. This equates to a maximum loss of ~2% of body nitrogen d −1 . Excretion rates decreased during the 1‐d periods without food, and rates during the feeding periods were ~30% higher than in those without food. This suggests that the lack of feeding in traditional experiments leads to roughly 30% underestimates of excretion rate. These results help to set some limits on ammonium production rates of South Georgia krill over regional scales. Our calculations suggest that the role of krill in this varies between habitats to the west of the island (insignificant) and those in the east (significant).

Evaluation of the Best disease gene in patients with age-related macular degeneration and other maculopathies - R. Allikmets; Johanna M. Seddon; Paul S. Bernstein; A. Hutchinson; Andrew Atkinson; Sanjay Sharma; Bernard Gerrard; W. Li; Michael L. Metzker; Claes Wadelius; C. Thomas Caskey; Michael Dean; et al. (Human Genetics, 1999)

An integrated genetic linkage map of the laboratory rat - Donna M. Brown *, , Tara C. Matise; George Koike; Jason S. Simon; Eric S. Winer; Sarah Zangen; Michael G. McLaughlin; Masahide Shiozawa; O. Scott Atkinson; James R. Hudson, Jr.; Aravinda Chakravarti; Eric S. Lander **, , Howard (Mammalian Genome, 1998)

Enhanced transgenic plant resistance to nematodes by dual proteinase inhibitor constructs - Peter E. Urwin; Michael J. McPherson; Howard J. Atkinson (Planta, 1998)